2022
DOI: 10.3390/nano12224096
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-FET’s Phase-Transition-Materials Design Guidelines for Ultra-Low Power Applications at 3 nm Technology Node

Abstract: In this work, a hybrid-phase transition field-effects-transistor (hyper-FET) integrated with phase-transition materials (PTM) and a multi-nanosheet FET (mNS-FET) at the 3 nm technology node were analyzed at the device and circuit level. Through this, a benchmark was performed for presenting device design guidelines and for using ultra-low-power applications. We present an optimization flow considering hyper-FET characteristics at the device and circuit level, and analyze hyper-FET performance according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The parameters of PTM used for designing the hybrid-CMOS inverter have been documented in table 2, showing the alterations made from those originally provided in table 1. The parameters follow all the device design-related constraints [3,9]. The circuit design in figure 2 is implemented and simulated in the analog design environment of the cadence tool.…”
Section: Circuit Design Of Proposed Hybrid-cmos Invertermentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of PTM used for designing the hybrid-CMOS inverter have been documented in table 2, showing the alterations made from those originally provided in table 1. The parameters follow all the device design-related constraints [3,9]. The circuit design in figure 2 is implemented and simulated in the analog design environment of the cadence tool.…”
Section: Circuit Design Of Proposed Hybrid-cmos Invertermentioning
confidence: 99%
“…Once the current begins to decrease and reaches the metallic-to-insulating critical current (I C-MIT ), the material switches back to the metallic state [2]. Considerable research is currently underway to investigate the practicality of phase transition material (PTM) in creating low-power circuits [3]. Notably, recent studies have revealed the potential of employing PTM in designing low-power circuits specifically tailored for medical devices [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the lower the SS value, the greater the change in current, even if the gate voltage is slightly adjusted, the lower the power consumption in the off state. However, the Boltzmann theory states that the basic limit of SS at room temperature is 60 mV/dec, which is a significant barrier to lowering the operating voltage of conventional metal oxide semiconductor field effect transistors (MOSFETs) [ 4 , 5 , 6 , 7 , 8 , 9 ]. Considering the unit of SS value, it means the size of gate voltage required for the drain current value to increase by 10 times.…”
Section: Introductionmentioning
confidence: 99%